Estimation of Nuwiq® (simoctocog alfa) activity using one‐stage and chromogenic assays—Results from an international comparative field study. Issue 4 (20th May 2019) - Tiefenbacher, Stefan; Albisetti, Manuela; Baker, Peter; Kappert, Guenther; Kitchen, Steve; Kremer Hovinga, Johanna A.; Pouplard, Claire; Scholz, Ute; Ternisien, Catherine; Borgvall, Carin; Vicente, Tiago; Belyanskaya, Larisa; et al.
Abstract: Background: Accurate determination of coagulation factor VIII activity (FVIII:C) is essential for effective and safe FVIII replacement therapy. FVIII:C can be measured by one‐stage and chromogenic substrate assays (OSAs and CSAs, respectively); however, there is significant interlaboratory and interassay variability. Aims: This international comparative field study characterized the behaviour of OSAs and CSAs used in routine laboratory practice to measure the activity of Nuwiq ® (human‐cl rhFVIII, simoctocog alfa), a fourth‐generation recombinant human FVIII produced in a human cell line. Methods: FVIII‐deficient plasma was spiked with Nuwiq ® or Advate ® at 1, 5, 30 and 100 international units (IU)/dL. Participating laboratories analysed the samples using their routine procedures and equipment. Accuracy, inter‐ and intralaboratory variation, CSA:OSA ratio and the impact of different OSA and CSA reagents were assessed. Results: Forty‐nine laboratories from 9 countries provided results. Mean absolute FVIII:C was comparable for both products at all concentrations with both OSA and CSA, with interproduct ratios (Nuwiq ® :Advate ® ) of 1.02‐1.13. Mean recoveries ranged from 97% to 191% for Nuwiq ®, and from 93% to 172% for Advate ®, with higher recoveries at lower concentrations. Subgroup analyses by OSA and CSA reagents showed minor variations depending on reagents, but no marked differences between the two products. CSA:OSA ratios based on overall means ranged from 0.99 to 1.17 for Nuwiq ® and from 1.01 to 1.17 for Advate ® . Conclusions: Both OSAs and CSAs are suitable for the measurement of FVIII:C of Nuwiq ® in routine laboratory practice, without the need for a product‐specific reference standard.